Analisis Afek Variasi Interpersonal dengan Model Dialektologi dalam Talk Show Mata Najwa On Stage - Windi Erica Sari; Gigit Mujianto (ESTETIK : Jurnal Bahasa Indonesia, 2021)
This study aims to identify the form of the social character of the interpersonal affect and the phonological features of the dialectology of the presenter and informants in the Talk Show Mata Najwa On Stage "Semua Karena Ahok". This research is a qualitative descriptive study using a functional linguistic approach.Â  Sources of data from this study were obtained from conversations conducted by Najwa Shihab and Basuki Tjahaja Purnama (Ahok). The results of the research on the Talk Show Mata Najwa on Stage episode "Semua Karena Ahok" show:Â  1) there are six forms of social characters with interpersonal effects, namely: trustworthiness, fairness, caring, respect, citizenship, responsibility. All the six characters were found in Najwa and Ahok. It could be seen from everything that was done on the Talk Show Mata Najwa On Stage "Semua Karena Ahok". Positive affect could be seen with words, phrases and sentences that showed the social character of the positive interpersonal effects they have. The assessment that showed a positive character could be seen from the intensity carried out by Najwa and Ahok. Najwa Shihab and Ahok's intensity is often proven by the many conversations shown. 2) there are dialects which were influenced by regional languages based on dialectological phonological characteristics, among others: Seribu: vowel phoneme /i/ becomes [e]= Serebu. Ribu: vowel phoneme /i/ becomes [e]= Rebu. Ramai: vowel phoneme /a/ becomes [e] and release of consonant phonemes= Rame. Kita: vowel phoneme /i/ becomes [e]= Kite. Iya: vowel phoneme /i/ becomes [e]= Iye